What drives the Quotes of Earnings Forecasters? - Bert de Bruijn; Philip Hans Franses (Tinbergen Institute, 2012)
Earnings forecasts can be useful for investment decisions. Research on earnings forecasts has focused on forecast performance in relation to firm characteristics, on categorizing the analysts into groups with similar behaviour and on the effect of an earnings announcement by thefirm on future earnings forecasts. In this paper we investigate the factors that determine the value of the forecast and also investigate to what extent the timing of the forecast can be modeled. We propose a novel methodology that allows for such an investigation. As an illustration we analyze within-year earnings forecasts for AMD in the period 1997 to 2011, where the data are obtained from the I/B/E/S database. Our empirical findings suggest clear drivers of the value and the timing of the earnings forecast. We thus show that not only the forecasts themselves are predictable, but that also the timing of the quotes is predictable to some extent.
urn:NBN:nl:ui:15-1765/34710
Keywords: G17; G24; M41; 330; Earnings Forecasts; Earnings Announcements; Financial Markets; Financial Analysts; Spekulation; Kapitaleinkommen; Prognose; Finanzanalyse; Bayes-Statistik; Welt